Evaluating Inter-Faith Initiatives: A Cambridge Case Study - McCallum, Richard (Studies in interreligious dialogue, 2017)
This is the second of a pair of articles exploring the much neglected issue of evaluation with respect to inter-faith initiatives. The first article looked at the current state of inter-faith evaluation in the literature and proposed a framework for such evaluation. This second article presents a case study utilizing the framework to evaluate the Cambridge Inter-faith Programme summer schools that took place from 2011 to 2015. It presents the data gathered over this period, explores the representational, relational, epistemic and existential changes observed amongst the students as a result of the school, and evaluates the practical outcomes of the program. It finds that the schools generally increased rather than decreased the participants' sense of religious identity, yet helped them to form ongoing relationships with others and resulted in continued or increased inter-faith engagement.